2009
DOI: 10.1080/17470910802625215
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects on mirror approaching behavior and neurochemical aspects of the telencephalon in the fish, medaka (Oryzias latipes)

Abstract: Shoaling can be considered a simple form of affective behavior displayed by social fish in which a single fish exhibits an tendency to approach others. In the present study, we adopted a dual approach to investigate shoaling behavior in the medaka fish (Oryzias latipes): a behavioral pharmacological approach to assess mirror approaching behavior and an immunohistochemical approach to examine the neurotransmitter distribution in the medaka telencephalon. In order to gain an insight into shoaling activity, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Previous studies have shown a behavioral effect of diazepam on fish (Rehnberg et al, 1989;Corrêa and Hoffmann, 1999;Bencan et al, 2009;Tsubokawa et al, 2009;Gebauer et al, 2011), but animals were exposed to very high concentrations, and reproduction was not measured. Exposure to diazepam has been shown to induce aneuploidy in both human and mouse sperm; a severe condition that can generally result in birth defects (Schmid et al, 1999;Baumgartner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a behavioral effect of diazepam on fish (Rehnberg et al, 1989;Corrêa and Hoffmann, 1999;Bencan et al, 2009;Tsubokawa et al, 2009;Gebauer et al, 2011), but animals were exposed to very high concentrations, and reproduction was not measured. Exposure to diazepam has been shown to induce aneuploidy in both human and mouse sperm; a severe condition that can generally result in birth defects (Schmid et al, 1999;Baumgartner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in zebrafish, diazepam at respective concentrations of 1.25 and 0.16 mg L 21 can have anxiolytic effects measured as reduced novel tank diving response (Bencan et al, 2009) and shoal cohesion (Gebauer et al, 2011). A reduction in shoaling behavior was observed in medaka exposed to diazepam at concentrations of 15 mg kg 21 of body weight, suggesting that diazepam decreased the anxiety of isolation (Tsubokawa et al, 2009). In zebrafish, 0.05 mg L 21 of diazepam suppressed the typical preference for the edge of the tank (Richendrfer et al, 2012), and a 2.5 mM concentration decreased the typical dark-avoidance behavior during the light/dark preference test (Steenbergen et al, 2011) showing an anxiolytic effect of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Medaka ( Oryzias latipes ) exhibit prominent shoaling behavior. For example, a single medaka fish tends to approach a conspecific group [14] as well as a mirror image of its own figure [15]. (2) When medakas form a school, individual fish tend to maintain a nearest-neighbor distance [16],[17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many fish display a systematic preferential use of one eye, and their laterally placed eyes influence their everyday behaviour (Tsubokawa et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Mirror images are often used to investigate fish predator inspection (Milinski 1987), but a social response to this stimulus has also been observed (Meliska et al 1980;Miklosi et al 1998). Furthermore, many fish display a systematic preferential use of one eye, and their laterally placed eyes influence their everyday behaviour (Tsubokawa et al 2009). Our goal was to measure the responsiveness of D. labrax to its mirror image.…”
Section: Mirror Testmentioning
confidence: 99%